A life table for female barren-ground caribou in north-central Canada - Thomas, Donald C.; Barry, Samuel J. (Rangifer, 1990)
A survivorship curve and cohort-specific life table were developed for female barren-ground caribou (Rangifer tarandus groenlandicus) sampled from the Beverly herd from 1980 through 1987. Significant (P < 0.05)differences among yearly samples in the age distributions of females>2.5 years old were attributed to sampling error and real cohort size fluctuations caused by variations in productivity. Pooled data overcame much of that variation and the resultant quadratic-fit curve and life table are believed to yield about average survival/mortality statistics over the 8-year sampling period. Mortality rates increased progressively from 10.6% between age 2 and 3 years to 22.4% between age 10 and 11 years and accelerated thereafter.